(3GdeONd ddYdhe GdbGfhfjI(B((3ehLR GdfXQjI GdYGeI ddbGfhf hGdfXQjI GdYGeI ddMb(B)s - (3Jhajb MSf(B, (3aQLs ((3GdGScfOQjI(B:s (3eDSSI GdKbGaI GdLGeYjI(B,s)
(3aj fXQjI GdbGfhf,GdJYQja HGdbGfhf hNUGFUg hhVYg ef GdbhGYO GdGLJeGYjI GdCNQi hfWGbg,JbSje GdbGfhf(B((3CfhGY GdbhGYO GdbGfhfjI(B)(3,eUGOQ GdbGfhf,JWHjb GdbGfhf,GdJYQja HGdMb hCfhGY GdMbhb hJbSjeGJgG, CQcGf GdMbs
Keywords: (3GdbGfhfs